Partis en Hainaut? La place de la noblesse hainuyère dans la lutte entre Jacqueline de Bavière et Jean IV de Brabant (1424-1428) - Flammang, V. (BMGN - Low Countries Historical Review, 2008)
Hainault Factions? The Role of the Hainault Nobility in the Struggle between Jacqueline of Bavaria and John IV of Brabant (1424- 1428)From March until June 1425, part of Hainault was devastated by the war that was waged between Jacqueline of Bavaria, heiress to the county, and her exhusband, John IV of Brabant, both of whom were pretenders to the sovereignty of the county. On this occasion, part of the county's nobility split up and chose to support one of the opposing sides. Among the various incentives that might have influenced the nobles, two predominant elements seem to have motivated their choice of camp: the territorial base of the nobles concerned and John IV's personality. The weakness of his character may have attracted some nobles who planned to take advantage of the situation or, conversely, it may have failed to please some members of the high-ranking and ancient nobility of Hainault, among whom chivalric ideals were still very much alive. This article is part of the special issue 'The history of the nobility in the Netherlands and Belgium'.